Movement patterns of juvenile green sturgeon (Acipenser medirostris) in the San Francisco Bay Estuary - Michael J. Thomas; Andrew L. Rypel; Gabriel P. Singer; A. Peter Klimley; Matthew D. Pagel; Eric D. Chapman; Nann A. Fangue (Environmental Biology of Fishes, 2022)
Little is known about the distribution and ecology of juvenile green sturgeon throughout their range and specifically within California’s Central Valley and the San Francisco Bay Estuary. The objective of our study was to identify rearing movement patterns of juvenile green sturgeon and their interaction with Delta and Bay habitats. Acoustic biotelemetry was used to record juvenile movements and residence within different regions of this highly modified watershed. We document a diversity of movements exhibited by 31 acoustically tagged juvenile green sturgeon monitored over a 9-month period. The juvenile sturgeon either (1) remained in the Delta or moved (2) into the Carquinez Straits, (3) into San Pablo Bay, (4) into San Pablo Bay but returned to Delta, (5) through the estuary and likely left through the mouth of the bay, (6) or left the estuary only to return later. Spatiotemporal habitat quality varies within and between Delta and Bay habitats. Variation in water year and hydrologic connectivity are likely to influence habitat quality and quantity, and behaviors may be differentially optimized for fitness in response to environmental variation. Our results provide initial evidence supporting multiple behavioral movement patterns and a broad use of regional habitats for green sturgeon in the California Central Valley. This apparent behavioral diversity observed through movement patterns may ensure long-term success of all population segments over time in an extremely variable environment, ultimately supporting overall population stability (i.e., the portfolio effect). Enhanced conservation efforts may be needed to protect juvenile green sturgeon and the habitats they rely upon.